2018
DOI: 10.1016/j.jid.2017.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Mediate Tissue Injury in the Autoimmune Skin Disease Bullous Pemphigoid

Abstract: Eosinophils are typically associated with unique inflammatory settings, including allergic inflammation and helminth infections. However, new information suggests that eosinophils contribute more broadly to inflammatory responses and participate in local immune regulation and the tissue remodeling/repair events linked with a variety of diseases. Eosinophilic infiltration has long been a histologic hallmark of bullous pemphigoid (BP), a subepidermal autoimmune blistering disease characterized by autoantibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 54 publications
3
88
0
3
Order By: Relevance
“…Murine models expressing humanized FcεRI and NC16a, the major epitope in BP180, identified IgE‐mediated tissue destruction proceeds through eosinophil activation. Disease severity in this model correlated with IgE levels and identified eosinophils as the major IgE activated effector cells necessary for blister formation . The significance of IgE autoantibodies in BP however remains controversial as they are not universally detected and are not associated with a specific BP phenotype .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 82%
See 1 more Smart Citation
“…Murine models expressing humanized FcεRI and NC16a, the major epitope in BP180, identified IgE‐mediated tissue destruction proceeds through eosinophil activation. Disease severity in this model correlated with IgE levels and identified eosinophils as the major IgE activated effector cells necessary for blister formation . The significance of IgE autoantibodies in BP however remains controversial as they are not universally detected and are not associated with a specific BP phenotype .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 82%
“…Increased expression of eotaxin‐1 in lesional skin and a serum to lesional gradient in BP patients drives eosinophil infiltration and explains the high concentrations in cellular infiltrates . Eosinophils have a clear pathogenic role in BP . As such, inhibition of its chemotactic signals provides a promising avenue for therapeutic benefit.…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…However, the pathogenicity of BP230 IgE has not been studied. The pathogenic role of anti‐BP230 IgE may be elucidated by injection of anti‐BP230 IgE into the humanized IgE receptor eosinophil model as suggested for anti‐hNC16A IgE‐induced BP in the future …”
Section: In Vivo Studies Of Autoantibodies Against Bp230mentioning
confidence: 99%
“…Previous studies have reported the relevance of eosinophils in the pathogenesis of BP. Increasing evidence has been presented on the pathogenic role of eosinophils in BP in mediating tissue damage (Lin et al, ; Moriuchi, Nishie, Ujiie, Natsuga, & Shimizu, ). It was considered that eosinophils, the major actors in the pathogenesis of BP, would inspire novel perspectives for a targeted therapy (Simon, Borradori, & Simon, ).…”
mentioning
confidence: 99%